EFEKTIVITAS PENGGUNAAN VIDEO ANIMASI TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS V SD MUHAMMADIYAH AMBARBINANGUN - Septiyaningtiyas, Hanin Dewi; Komalasari, Mahilda Dea (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The success of the learning process is significantly influenced by the students' enthusiasm in what they are studying. Students' focus and excitement for studying may be increased by using interactive and captivating learning resources. Animated video is one such medium as it makes the content easier to understand and shows it graphically. Thus, the purpose of this study was to ascertain how well animated video content affected fifth-grade science students' attention. In this work, an experimental method was combined with a quantitative approach. A control class and an experimental class, each with 24 pupils, made up the sample. A learning interest questionnaire was employed for data collection, and it was given as a pretest and posttest. Independent sample t-tests, homogeneity tests, and normality tests were used to examine the data. According to the findings, the experimental class's average posttest score was 43.04167, which was higher than the control group's average score of 38.54167. The significance value (Sig. 2-tailed) obtained from the hypothesis test was 0.009 < 0.05. Therefore, it can be said that using animated video content increases fifth-grade kids' interest in studying science. Keywords: animated video, interest in learning, science.